The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/msj.20196
|View full text |Cite
|
Sign up to set email alerts
|

Joseph's Wishes: Ethical Decision‐Making in Duchenne Muscular Dystrophy

Abstract: The death of a child is an uncommon occurrence and can be difficult for families to accept. Attempts by the healthcare team to discuss end-of-life issues can be so upsetting to families that they refuse to participate in the discussion. Even with diseases where an early death can be anticipated, such as Duchenne muscular dystrophy, the family is often reluctant to discuss end-of-life issues when the patient is relatively healthy, preferring to focus on the current health issues. In this article we discuss what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 9 publications
1
19
0
2
Order By: Relevance
“…The neuroethical issue is particularly important within the decision-making conflict regarding the suspension of respiratory care. In accordance with many authors 19,20,25,55 , in dealing with patients that suffer from severe cognitive sequelae (cerebral malformations, persistent coma, cerebral palsy, and so forth), doctors felt less discomfort in recommending the suspension and omission of treatment procedures than when dealing with non-oncological illnesses that do not affect the patient cognitively, such as neurodegenerative muscular disorders 28,54,67 , cystic fibrosis 46 , and pulmonary insufficiency due to hemosiderosis 37 and so forth. However, with respect to chromosomopathies and/or cerebral malformations, other studies 12,76 defend the position that the diagnosis in and of itself is not sufficient to recommend the implementation of therapeutic restrictions.…”
Section: Current Treatments That Will Be Suspended/ Renouncedsupporting
confidence: 54%
See 1 more Smart Citation
“…The neuroethical issue is particularly important within the decision-making conflict regarding the suspension of respiratory care. In accordance with many authors 19,20,25,55 , in dealing with patients that suffer from severe cognitive sequelae (cerebral malformations, persistent coma, cerebral palsy, and so forth), doctors felt less discomfort in recommending the suspension and omission of treatment procedures than when dealing with non-oncological illnesses that do not affect the patient cognitively, such as neurodegenerative muscular disorders 28,54,67 , cystic fibrosis 46 , and pulmonary insufficiency due to hemosiderosis 37 and so forth. However, with respect to chromosomopathies and/or cerebral malformations, other studies 12,76 defend the position that the diagnosis in and of itself is not sufficient to recommend the implementation of therapeutic restrictions.…”
Section: Current Treatments That Will Be Suspended/ Renouncedsupporting
confidence: 54%
“…Torres et al 69 elucidated that the removal of the patient's tubes, within the context of palliative care, must only occur after the patient has been off muscle relaxers, receives higher doses of sedatives or has had his ventilatory parameters decreased until the moment the tubes are removed and are substituted by some other less invasive respiratory care procedure, such as nasal oxygen cannulas. However, Penner et al 54 , upon studying a case of Duchenne muscular dystrophy, showed that it is not clear if mechanical ventilation within the patient's home via tracheostomy constitutes therapeutic obstinacy, or if it is simply a chronic form of care in the face of a severe and knowingly fatal disease.…”
Section: Current Treatments That Will Be Suspended/ Renouncedmentioning
confidence: 99%
“…Two case series252 267 report on positive experiences of children and young adults with DMD in the formulation of life plans, regardless of the decision made about long-term ventilator assistance. A case study of a boy with DMD by Penner and colleagues268 describes the ethics of disclosure and emotionally charged challenges surrounding advance care plans.…”
Section: Qol and Palliative Carementioning
confidence: 99%
“…Penner, Cantor, and Siegal [40] reported the determination of a young man with DMD who decided not to use his long-term ventilator. His mother was shocked and rejected his decision at first, but she later accepted this decision due to the medical team's efforts to include her in the end-of-life conversation.…”
Section: Parents' Intervention In the Development Of Self-determinatimentioning
confidence: 99%